1972
DOI: 10.1002/macp.1972.021520125
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐chain competition kinetics in linear polymers

Abstract: Recent data of STEPTO and WAYWELL for ring-chain competition in the kinetically controlled polymerizing system ( i e . backward rate = 0) of (polyethylene glycol)/(hexamethylene diisocyanate) have been fitted by exact computer calculations, assuming GAUSSian chain statistics. A good one-parameter fit is obtained. The optimum value of the parameter is compared with theory. The results suggest that the solvent used (benzene at 7OoC) is thermodynamically poor for this polymer system. ZUSAMMENFASSUNG:Neuere Daten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 11 publications
(1 reference statement)
6
79
0
Order By: Relevance
“…[110][111][112][113] In principle, should all the end-groups be fully consumed (i.e., 100% conversion of end-groups) then all polymer chains should consist of a cyclic topology, assuming stoichiometric amounts of end-groups. Scheme 1 shows the diffusion effects for the competing reactions for step-growth versus cyclization, in which step-growth will dominate the kinetics over cyclization as molecular weight is increased.…”
Section: Ring-closure Reactionsmentioning
confidence: 99%
“…[110][111][112][113] In principle, should all the end-groups be fully consumed (i.e., 100% conversion of end-groups) then all polymer chains should consist of a cyclic topology, assuming stoichiometric amounts of end-groups. Scheme 1 shows the diffusion effects for the competing reactions for step-growth versus cyclization, in which step-growth will dominate the kinetics over cyclization as molecular weight is increased.…”
Section: Ring-closure Reactionsmentioning
confidence: 99%
“…Product analysis showed the formation of significant proportions of cyclic oligomers and extrapolation of their data indicated that such products increased to 100% at complete conversion, in general agreement with the predictions of JS theory. Gordon and Temple analysed the system further in terms of reaction kinetics [46], and graph theory [47]. Subsequently, Stanford et al adopted a statistical approach to rate theory [48].…”
Section: General Considerationsmentioning
confidence: 99%
“…Further studies in this direction were summarized in two review articles. [9,10] Between 1970 and 1980 Stepto and coworkers, [11,12] and Gordon and coworkers [13,14] conducted speculative calculations of the kinetics of step-growth polymerizations assuming that cyclization competes with each chain-growth step. Those authors also concluded that 100% conversion should yield 100% of cyclic reaction products.…”
Section: Introductionmentioning
confidence: 99%